Elke Otte Hülse: ancestral narratives and expanded tapestry techniques (Palíndromo, 2020)
Tapestries comprise and can be considered as a narrative form of ancestral art, which is of great importance in history, and in the contemporary, we find artists who extrapolate and expand the technique, problematizing concepts and issues pertinent to it. Elke Otte Hülse, a Santa Catarina artist with international traffic, breaks geographical boundaries and bound-aries of ignorance of this secular technique and is presented along with a brief history of tapestry, with the purpose of presenting its actuality.
Keywords: Elke Otte Hülse; tapestry; art history; history of the tapestry; narrative